AB0268 Coronary Artery Stenosis in Patients with Rheumatiod Arthritis. (15th July 2016) - Gerasimova, E.; Popkova, T.; Novikova, D.; Fomicheva, O.; Kolmakova, D.; Nasonov, E.
Abstract : Background: Rheumatoid arthritis (RA) is a systemic inflammatory disease characterized by increased cardiovascular morbidity and mortality. Coronary angiography (CAG) is the gold standard to identify and assess the degree of coronary artery (CA) involvement. CA diseases (CAD) development in RA patients (pts) is associated with the accumulation of traditional risk factors and immunological disorders. Objectives: To determine the incidence and predictors of CA stenosis development in RA pts with suspected CAD. Methods: To analyze 63 RA pts (male/female 25/38, mean age 58 [52; 63] years, with long-standing RA (10, 5 [7; 23] years), moderate to high clinical disease activity DAS 28 =4, 7 [3, 3; 5, 8]). All pts underwent CA angiography. Multiple regression analysis was used to determine the risk of CA stenosis in RA pts. Results: CA stenosis was detected in 22 (35%) of the 63 pts, male/female 15/7 (I group), including single vessel involvement - in 15 (68%) pts, three-vessel damage - in 7 (32%) pts, without cases of documented two vessels lesions. The most common stenosis location was the middle segment of the left anterior descending artery (11 (50%) pts), the right coronary artery (RCA) was more rarely involved, and RCA stenosis was observed in 7 (33%) pts, stenosis of the middle RCA segment - in 9 (41%) out of 22 pts. In 41 (65%) out of 63 pts hemodynamically insignificant stenoses (<50%) or intact CA was documented, male/female 10/31 (II group). Groups were comparable in terms of age, disease duration and DAS 28 scores. Males prevailed in Group 1: 68% vs 24% in Group 2 ( p <0, 05). Detection rates of carotid artery atherosclerotic plaques and thickening of the intima-media were similar in Groups 1 and 2 (19/16% and 53/56% pts). The prevalence of traditional risk factors was also similar in both groups: hypertension - 77% and 88%, dyslipidemia - 26% and 33%, diabetes mellitus - 5% and 17%, smoking – 45% and 17%, physical inactivity - 58% and 42%, obesity - 45% and 32% pts in Group 1 and 2, respectively. Serum HDL cholesterol concentrations in Group 1 (1, 2 [1, 0;1, 5]mmol/l) was lower, than in Group 2 (1, 55 [1, 3;2, 0]mmol/l, p =0, 03), while concentrations of cholesterol, LDL cholesterol and triglycerides did not differ in between the groups. There were no differences in therapeutic and dosing regiments (disease-modifying antirheumatic drugs (DMARDs), GEBAs and oral glucocorticiods (GCs)), with the only exclusion: the duration of GCs therapy was higher in Group 1 pts (5, 3 [4;12] years) vs (3, 1 [1, 5;8], p <0, 05) Group 2. The multiple regression analysis did not establish any direct relationship between CA stenosis and gender, age, RA activity, cholesterol and LDL cholesterol concentrations, use of DMARDs and oral GCs. Age was the strongest, but not statistically significant variable predicting stenosis (odds ratio (OR) 0, 85; 95% CI [0, 72–1, 0], p =0, 05), with the following HDL-C <1, 2mmol/L for women and <1, 0 mmol/L for men (OR 0, 82; 95% CI [0, 64–0, 90], p =0, 09). Conclusions: Male gender, low HDL cholesterol levels and long-term GCs use seem to increase the risk of coronary artery stenosis in RA pts. Disclosure of Interest: None declared